Writing the Imperial Experience of Hunting: Assam Planter and the Sensory World of a British Tea Frontier. Issue 5 (3rd September 2021) - Baruah, Manjeet
Abstract: Hunting encompasses a range of sensory experiences such as sight, smell and taste (game as food). On the tea frontier of British Assam, such a sensory world of hunting was closely connected to the ideas and practices of empire, as well as to the production of the global commodity of tea. In this regard, A.R. Ramsden's memoir, Assam Planter: Tea Planting and Hunting in Assam (1945), provides a rich illustration of sensory experiences in the making of such a tea frontier and a global commodity. Furthermore, the memoir is constituted through the complex interplay of senses that is mapped onto the plantation social order. In the process, the sensory experiences of the 'sahib' and the 'native' are organised in an imperial narrative of tea and frontier-making. Yet, given its historical moment, the context of imperial crisis is also reflected in the memoir through the contradictions of sensory experiences and, thereby, the problems faced in producing the imperial narrative of tea and frontier-making.